Cryotherapy as an Adjunct to Cleaning and Shaping in Endodontics: A Review - Shivangi Vats1 , Vinod Jathanna2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cryotherapy refers to treatments that are done at reduced temperatures. In the recent times, Cryotherapy hasfound use in the field of endodontics during root canal irrigation, primarily to reduce post-operative painafter non-surgical endodontic therapy. In this review, we are throwing some light over use of Cryotherapy inroot canal irrigation, its clinical implications along with positive and negative side effects based on currentlyavailable literature. Vital pulp cryotherapy is a process in which sterile water ice shavings are applied onexposed pulp tissue. Cryogenic fluid, when used as an irrigant has shown efficacy in antibacterial actionas it can reach the desired depth and bring about immediate freezing of bacterial cells along with theirsubsequent Cryodestruction. Use of cold saline solution (2.5 0 C) as the final irrigant brings about reductionin external root surface temperature by more than 100C for 4 minutes, which might be produce a local antiinflammatory effect in the periradicular tissues. In addition, Various clinical and experimental studies havehighlighted the role of Cryoirrigation in controlling post-operative pain after endodontic therapy